2014
DOI: 10.1590/s1679-45082014ao3119
|View full text |Cite
|
Sign up to set email alerts
|

Audiological findings in aphasic patients after stroke

Abstract: Objective To outline the audiological findings of aphasic patients after cerebrovascular accidents.Methods This is a cross-sectional study performed between March 2011 and August 2012 in the Speech, Language, and Hearing Pathology Department of the Universidade Federal de São Paulo. A total of 43 aphasic subjects (27 men) were referred for audiological evaluation after stroke, with mean age of 54.48 years. Basic audiological evaluation tests were performed, including pure tone audiometry, speech audiometry (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies have found high rates of untreated hearing loss in people with aphasia. [24][25][26] Lassig et al reported that 21% (n ¼ 15) of the 72 patients with aphasia following lefthemisphere ischemic stroke who were able to be tested using pure tone audiometry had a hearing loss and were not wearing hearing aids. 25 Formby et al measured hearing levels in 243 people aged 30 to 103 years (mean age % 70 years) who had had a single stroke and concluded that the rate of hearing loss was more than that seen in healthy controls, but similar to rates of hearing loss for older people in residential care.…”
Section: Stroke and Hearing Lossmentioning
confidence: 99%
“…Several studies have found high rates of untreated hearing loss in people with aphasia. [24][25][26] Lassig et al reported that 21% (n ¼ 15) of the 72 patients with aphasia following lefthemisphere ischemic stroke who were able to be tested using pure tone audiometry had a hearing loss and were not wearing hearing aids. 25 Formby et al measured hearing levels in 243 people aged 30 to 103 years (mean age % 70 years) who had had a single stroke and concluded that the rate of hearing loss was more than that seen in healthy controls, but similar to rates of hearing loss for older people in residential care.…”
Section: Stroke and Hearing Lossmentioning
confidence: 99%
“…In another study 7 , only the transient otoacoustic emissions were investigated in aphasic individuals, in which 44.2% of them presented the absence of TEOAE in one or more frequencies, either early detecting alteration in the cochlea or confirming the already existing alteration.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these presentations such as cortical deafness are rare but quite dramatic and would not go undetected. Other presentations may be subtler and only be detected by detailed questioning of the patient and by precise psychoacoustic and electrophysiological testing; however, they may still have a significant impact on listening, linguistic skills, and overall communication of the affected patient (Häusler and Levine, 2000;Bamiou et al, 2012;Onoue et al, 2014).…”
mentioning
confidence: 99%